1996
DOI: 10.1037/0022-0167.43.4.456
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of therapist experience and personal characteristics to the working alliance.

Abstract: The authors hypothesized that level of experience and selected personal characteristics of therapists would predict clients' perceptions of the working alliance early in treatment. Therapists (N = 73) in university settings completed measures that assessed level of self-directed hostility, perceived social supports, and degree of comfort with attachment, and their clients completed a measure that estimated the working alliance between the 3rd and 5th sessions of therapy. As predicted, level of self-directed ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
137
1
10

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(160 citation statements)
references
References 23 publications
12
137
1
10
Order By: Relevance
“…ment anxiety therapists endorsed, the more client ratings of the working alliance decreased over time. This finding is congruent with attachment theory (Bowlby, 1969(Bowlby, / 1982(Bowlby, , 1988, as well as with other clinical studies reporting that therapists' own attachment orientations influence the process of psychotherapy or the early working alliance (Dozier et al, 1994;Dunkle & Friedlander, 1996;Tyrrell et al, 1999). However, the current study extends this literature by moving beyond single-time-point assessments of the working alliance.…”
Section: Hlm Analyses Fixed Effectssupporting
confidence: 78%
See 1 more Smart Citation
“…ment anxiety therapists endorsed, the more client ratings of the working alliance decreased over time. This finding is congruent with attachment theory (Bowlby, 1969(Bowlby, / 1982(Bowlby, , 1988, as well as with other clinical studies reporting that therapists' own attachment orientations influence the process of psychotherapy or the early working alliance (Dozier et al, 1994;Dunkle & Friedlander, 1996;Tyrrell et al, 1999). However, the current study extends this literature by moving beyond single-time-point assessments of the working alliance.…”
Section: Hlm Analyses Fixed Effectssupporting
confidence: 78%
“…Dunkle and Friedlander (1996) reported that, early in treatment (between the 3rd and 5th sessions), therapists who reported comfort with intimacy were more likely to perceive more positive alliances with their clients. Elsewhere, Dozier, Cue, and Barnett (1994) found that clinical case managers' attachment style classifications were related to their clinical intervention strategies.…”
mentioning
confidence: 99%
“…Some therapists have been found to be more effective and better in alliance development than others (Lutz et al, 2007). Findings have pointed out that therapist experience alone is not significantly associated with the alliance (Dunkle & Friedlander, 1996;Kivlighan et al, 1998).…”
Section: Introductionmentioning
confidence: 68%
“…In the literature there are conflicting findings on therapy outcomes and the relationship to therapist experience level with some studies (e.g., Burlingame et al, 1989;Church, 1993;Gold & Dole, 1989) finding that experience does influence outcome and some studies (e.g., Clementel-Jones, Malan, & Trauer, 1990;Dunkle, 1996;Propst, Paris, & Rosberger, 1994) concluding that it does not influence outcome. In addition to including more therapists, perhaps as suggested by Elliot & Wexler (1994) future studies could be done that focus on therapists who regularly receive high ratings and their characteristics in order to shed more light on this debate.…”
Section: Limitationsmentioning
confidence: 99%